THE STRATEGIC ROLE OF BTN SYARIAH MARGONDA IN THE REALIZATION OF A USURY-FREE MURABAHA MORTGAGE AT PT. ABC GROUP: ANALYSIS BASED ON ISLAMIC LAW - Damanik, Ade Zuki; Noor, Afif; Ichrom, Mohamad (Universitas Islam Negeri Mataram, 2024)
This study aims to analyze the application of the murabaha contract in the BTN Syariah Margonda Home Ownership Credit (KPR) product from the perspective of Islamic law. In the face of increasing demand for usury-free housing, BTN Syariah offers a solution through the murabaha contract, which guarantees home financing without involving the element of interest. Through cooperation with PT ABC Group, BTN Syariah Margonda provides a more transparent and fair financing alternative for the community. This research method uses a normative-empirical approach with interviews, observations, and documentation studies. The results show that the application of the Murabaha contract at BTN Syariah Margonda is in accordance with Sharia principles, where the profit margin is determined from the start, and the installments are fixed throughout the payment period. However, the main challenge is the need for a more public understanding of the differences between sharia and conventional mortgages. Nevertheless, the murabaha contract provides a positive impact in the form of financial certainty for customers and supports stable financial planning without being trapped in usury practices. This research also identifies the need to increase public education on the advantages of Sharia-based financing and the importance of the role of property developers who fully implement Sharia principles.